The information needs of lecturers at the Cape Technikon and the ability of the Technikon Library to meet those needs - Kerkham, Andrew Summers (Library and Information Studies Centre (LISC), 2016)
Although the precursors of the South African technikons date back almost one hundred years, they became post-secondary institutions as recently as 1967. Their libraries have therefore had to be upgraded recently to meet the required educational level. With the technikon movement being so young, there has been little formal investigation of the information needs of the libraries' users. An investigation was therefore conducted into the information needs of lecturers at the Cape Technikon and the ability of the Library to meet those needs. The literature was examined and models formulated to clarify the concepts involved in (a) information and its communication, (b) users and their information needs, and (c) the evaluation of library services in their attempts to meet those needs. Previous studies were also examined to determine what variables should be examined. Various methodologies for an empirical investigation were considered; the survey method was chosen as most appropriate, and a questionnaire was developed to elicit lecturers' self assessment of the importance of specified information needs and their opinion of the Library's ability to meet those needs. Weighted average and percentage proportions were calculated and were used in producing tabulations of the data, profiles line graphs, histograms and pie charts. The data were then examined for inter-relationships; the results were compared with the results of previous surveys, and conclusions were drawn. The chief findings were that (a) discipline and work activity were the most important independent variables to influence information need; (b) work activity was determined largely by the need for technikon lecturers to change their subject fairly frequently, and by the low level of research at the time of the investigation; (c) the Library was an important source of information to the lecturers, and they were generally satisfied with the Library's services; (d) citation services were being under-utilised; (e) the Library proved to be inadequate in providing for a strong demand for monographs and for very recently published literature, in providing sufficient work and study space, and in providing adequate resources for research purposes. As a result the following recommendations were made: (a) the Library should provide a comprehensive literature searching and current awareness service for the many lecturers who were having to prepare lectures in new subject areas; (b) because of the importance of the Library to lecturers, it must be adequately staffed and financed; (c) attention must be given to the Library's ability to provide recently published literature, which may necessitate a reconsideration of the current collection development pol icy; (d) research must be encouraged, and the Library upgraded to provide the necessary resources for research.